Handheld photoacoustic imaging and sensing for 3D medical visualization - Liu, Siyu (Nanyang Technological University, 2020)
Medical imaging is a “magic” technique of creating a visual representation of the internal human body (hidden by the skin and bones) for clinical analysis and medical diagnosis. Photoacoustic imaging, a new-emerging medical imaging modality, is a powerful tool to perform five-dimensional imaging in the physiological environment by “listening to the sound of light”. Though the photoacoustic technique witnessed skyrocketing growth since its emergence, however, it has not been effectively applied in clinics. Though the photoacoustic technique takes advantage of the merits of both optical and ultrasound methods, it also integrates the system complexity of both sides, inevitable contributing to bulky and complicated system implementations. For the practical applications of the photoacoustic technique, handheld imaging was proposed and has been widely studied in the recent several years. However, the current-available handheld imaging systems all suffer various limitations, including trivial acoustic coupling, relatively large footprint, inhomogeneous photoacoustic sensitivity, low efficiency of photoacoustic field overlap, etc. To solve these problems, this thesis is mainly devoted to design and develop handheld photoacoustic imagers towards the clinical translation of the photoacoustic technique. In the light of interdisciplinary nature of the photoacoustic technique, the development of handheld photoacoustic 3D imagers requires effort in various aspects, including optical illumination design, acoustic detection design, back-end electronics design, imaging reconstruction algorithm development, and probe mechanical design. This Ph.D. thesis will comprehensively investigate the handheld photoacoustics in these above-mentioned aspects and present a set of developed handheld photoacoustic systems, including an all-in-one handheld photoacoustic 3D imager, a miniaturized handheld photoacoustic 3D imager, a portable photoacoustic sensing system, and a wearable photoacoustic 3D imager, in the sequence of step by step optimization. Particularly, with the aim of expanding the real-time capability of 3D handheld photoacoustic imaging, a GPU accelerated two-dimensional synthetic aperture focusing algorithm and a layered phase shift migration algorithm are further developed. In translating photoacoustic imaging from the conventional benchtop platform to a portable or even a wearable device, the proposed novel coaxial photoacoustic design and several developed handheld imagers are demonstrated to effectively miniaturize the imaging probe, reduce the system complexity, enhancing the usability, and may contribute more practical solutions to clinical applications of the photoacoustic technique. Some concepts and special designs may also inspire some interesting ideas inside or beyond the field of medical imaging.